Safe and serving school in troubled waters: A Christian-holistic approach to the pedagogical mission in times of rapid cultural change - van Olst, Peter (International journal of Christianity & education, 2025)
Due to rapid cultural change, schools in the Western world are facing a series of new challenges. Especially Christian schools need to find out how to adapt their personhood and character formation to the necessities of ethnical and directional pluralism. Invited or even obliged by governments and other partners, schools have to incorporate efforts for responsible citizenship, social cohesion, and sustainable development into their curricula. Investigating this dynamic empirically, this paper argues that Christian schools, to be both safe and serving, need to combine a strong focus on their pedagogical mission with a holistic approach of pupils and students.